Springboards to inquiry : 50 standards-based lessons for k-5 - Jaeger, Paige; Ratzer, Mary Boyd (Libraries Unlimited, An Imprint of ABC-CLIO, LLC, 2019)
This book delivers lesson plans for librarians to implement immediately, as is or with a little adaptation. Using the new AASL standards and an Information Literacy scope and sequence carefully crafted for K-6 students, the authors package lessons that are both engaging and challenging.